The Meaning of Life in the Perspective of Christian Theology and Existential Psychology: A Comparative Analysis of Rick Warren and Viktor E. Frankl - Jamson Siallagan; Yuliono Evendi; Irene Nur Arta Purba Siboro; Frans Aliadi; Daulat Marulitua Tambunan; Palima S. Sianipar (CV. Creative Tugu Pena, 2026)
The meaning of life is one of the fundamental questions of human existence that is increasingly relevant amid the identity and life purpose crisis of the modern generation. This study aims to conduct a comparative analysis of the thoughts of Rick Warren, a contemporary Christian theologian through his work The Purpose Driven Life, and Viktor E. Frankl, an existential psychiatrist with his logotherapy in Man’s Search for Meaning. Using a qualitative method based on literature study and comparative-descriptive analysis, this study highlights the points of convergence and fundamental differences between the two figures. Warren emphasizes that the meaning of life is only found in relationship with God and divine purpose through five main callings: worship, fellowship, discipleship, ministry, and mission. Meanwhile, Frankl asserts that the will to meaning is the primary motivation of humans, which can be realized through work, love, and attitudes toward unavoidable suffering. The findings show that although Warren is rooted in Christian theology and Frankl in existential psychology, both emphasize the dimension of transcendence, inner resilience, and personal responsibility as the core of a meaningful life. This study provides important contributions in the fields of theology, psychology, as well as the practice of education, spiritual ministry, and counseling, especially in responding to the crisis of life’s meaning faced by modern society.